2020
DOI: 10.36740/wlek202004121
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Structure of Acute Injury of Temporary and Permanent Frontal Teeth in Children, Analysis of Diagnostic and Treatment Measures and Their Effects

Abstract: The aim: To determine the structure of acute injuries of temporary and permanent frontal teeth in children, to analyze the applied diagnostic and treatment measures for acute tooth trauma and to investigate their effectiveness. Materials and methods: The subject of the study were 31 children aged 2-12 years with acute temporary and permanent tooth trauma. Methods: clinical (radiological, thermodiagnosis), medical and statistical. Results: The number of injured permanent teeth was greater than the number of inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Baena et al [25] conducted experiments on five sets of fixed splints using a universal testing machine and polarizing mirror, and observed that the glass fiber had better stress distribution around the affected teeth under different occlusal loads, and it could better distribute and absorb the occlusal stress from the center and edge. In clinical practice, some scholars [26][27] have confirmed that fiberband composite resin splint has a good effect on gingival index, plaque index, gingival crevicular bleeding, and the imaging examination of postoperative two-year follow-up. Zhu Wenting et al [28] found in the clinical observation of 320 cases of permanent anterior teeth that fiber composite resin has strong aesthetics and comfort, is easy to maintain good oral hygiene, and can ensure high bonding strength even if the adjacent teeth of the affected teeth are primary teeth.…”
Section: Elastic Fiber Composite Resin Splintmentioning
confidence: 99%
“…Baena et al [25] conducted experiments on five sets of fixed splints using a universal testing machine and polarizing mirror, and observed that the glass fiber had better stress distribution around the affected teeth under different occlusal loads, and it could better distribute and absorb the occlusal stress from the center and edge. In clinical practice, some scholars [26][27] have confirmed that fiberband composite resin splint has a good effect on gingival index, plaque index, gingival crevicular bleeding, and the imaging examination of postoperative two-year follow-up. Zhu Wenting et al [28] found in the clinical observation of 320 cases of permanent anterior teeth that fiber composite resin has strong aesthetics and comfort, is easy to maintain good oral hygiene, and can ensure high bonding strength even if the adjacent teeth of the affected teeth are primary teeth.…”
Section: Elastic Fiber Composite Resin Splintmentioning
confidence: 99%